Loving - Kingsbury, Karen (Kingsbury, Karen. Bailey Flanigan series, 2012)
In the fourth and final chapter in the Bailey Flanigan Series, Bailey is planning her dream wedding to Brandon Paul in Los Angeles. But doubts are wracking Bailey's mind. Did she make the right choice in choosing Brandon? Or should she return home to Bloomington, Indiana and be with Cody Coleman, her first love?